Reengineering Cracker-Dryer Machine Based on Fan speed and Temperature Considering Drying Time, Final Weight and Energy Consumption Factor - Emon Rifa'i; sabarudin ahmad; Anis Arendra; Rifky Maulana Yusron (Universitas Trunojoyo Madura, 2021)
Redesign and building a cracker drying machine should give priority to several factors to find the optimal point, one of which is by conducting experimental experiments. This research was carried out to find out from the tool and also pay attention to several things, such as temperature and fan speed. If one of these factors is ignored, it will not produce dry crackers and the dried crackers are less than optimal. The Independent parameters used in this research are temperature and fan speed. Dependent parameters used in this research are concerning drying time, final weight, and energy consumption. Design experiment using Factorial 3x3. Fan speed has 3 levels, they are 1000rpm, 1500rpm and 2000rpm. The Temperature parameter has 3 levels, they are 16, 19, and 21oC. Based on the design of experiment results, it was found that the drying time response for the combination that has the highest ranking is at a temperature of 19oC with a 2000rpm fan speed resulting in a drying time of 182,677 minutes.